The Role of Mudir in Preventing Cyberbullying Based on Islamic Educational Values at Al-Khairiyah Islamic Boarding School Cilegon - Eti Shobariyah; Taufiq Taufiq; Ofik Taufiqurrohman; Iis Faridah; Sapiudin Sapiudin (SYAMIL: Journal of Islamic Education, 2026)
The development of digital technology has brought significant changes to various aspects of human life. Along with these changes, the digital era also presents serious challenges, one of which is the increasing practice of cyberbullying. This study aims to analyze the strategies of the headmaster in reducing the challenges of cyberbullying through the implementation of Islamic educational values ”‹”‹in the Kesatrian Santri Taruna Islam Al-Khairiyah Citangkil environment as an effort to create a safe, healthy, and ethical digital environment based on Islamic values. This study uses a qualitative descriptive approach with a case study method through in-depth interviews and observations of the headmaster, students and administrators of the Islamic boarding school as well as documentation to produce relevant and accurate findings based on the research that has been conducted. The data analysis technique used refers to the analysis model proposed by Miles and Huberman. The analysis process includes several stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the headmaster implements a comprehensive and sustainable strategy by integrating Islamic educational values ”‹”‹into all aspects of Islamic boarding school life. This strategy not only focuses on controlling the use of digital technology, but also on developing the character and moral awareness of students in using digital media. The results of this study are expected to contribute to the development of adaptive educational strategies and policies that are appropriate for the digital era.